Towards Improved Organizational Governance of Neurotrauma Surveillance; Comment on "Neurotrauma Surveillance in National Registries of Low- and Middle-Income Countries: A Scoping Review and Comparative Analysis of Data Dictionaries" - Hanna E. Schenck; Halinder S. Mangat (Kerman University of Medical Sciences, 2023)
Neurotrauma surveillance data on burden and severity of disease serves as a tool to define legislations, guide highyield risk-specific prevention, and evaluate and monitor management strategies for adequate resource allocation. In this scoping review, Barthélemy and colleagues demonstrate the gap in neurotrauma surveillance in low- and middle-income countries (LMICs) and suggest strategies for governance in neurotrauma surveillance. We underline state accountability as well as the need for the close integration of academic and tertiary care clinical practitioners and policy-makers in addressing the public health crisis caused by neurotrauma. Additionally, multiple sources for surveillance must be included, especially in communities where victims may remain without access to formal healthcare. Finally, we offer insights into possible ways of increasing the visibility of neurotrauma on political agendas.